Study Of Coffee-Based Agroforestry Systems In Community Forests - Susanto, Anang; Harahap, Arman (International Journal of Science and Environment (IJSE), 2025)
Climate is an important factor in the growth and productivity of coffee plants. This research aims to determine the climate conditions regarding the use of shade on the development and productivity of coffee plants. This observation was carried out on agroforestry coffee plantations in Kare District, Madiun Regency. The coffee plants observed were 4 to 6 years old, and the shade used in the observations was Gamal, Dadap, and Sengon trees. Thus, based on the results of observations carried out over four months, it was found that the highest results were in Sengon stands, with an average of 27.2-27.7°C in January and March in terms of air temperature. Meanwhile, the highest observed humidity occurred in the first month and January at 76%. The highest wind speed occurs in April at 4 -5 km/hour. The highest intensity of light produced occurs in April at 8005 LUX. The results of these observations prove that the use of shade plants does not significantly affect the production and growth of coffee plants.